2021
DOI: 10.3390/s21020606
|View full text |Cite
|
Sign up to set email alerts
|

Structural Damage Identification Based on Integrated Utilization of Inverse Finite Element Method and Pseudo-Excitation Approach

Abstract: The attempt to integrate the applications of conventional structural deformation reconstruction strategies and vibration-based damage identification methods is made in this study, where, more specifically, the inverse finite element method (iFEM) and pseudo-excitation approach (PE) are combined for the first time, to give rise to a novel structural health monitoring (SHM) framework showing various advantages, particularly in aspects of enhanced adaptability and robustness. As the key component of the method, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The deformations obtained at the end of time integration are converted into strains for each PD material point with the formulas given in Eqs. (49)(50)(51). The strain values obtained here, namely the normal strains along the x -and y -axis and the xy -plane shear strains, are illustrated for both crack-free and crack-opening conditions as shown in Fig.…”
Section: Damage Detection and Crack Monitoring Of A Unidirectional Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…The deformations obtained at the end of time integration are converted into strains for each PD material point with the formulas given in Eqs. (49)(50)(51). The strain values obtained here, namely the normal strains along the x -and y -axis and the xy -plane shear strains, are illustrated for both crack-free and crack-opening conditions as shown in Fig.…”
Section: Damage Detection and Crack Monitoring Of A Unidirectional Th...mentioning
confidence: 99%
“…Particularly, the iQS4 element has recently gained a popularity for shape sensing applications on simple/complex geometries, e.g., ship and offshore structures [35][36][37][38][39] and stiffened aerospace panels [40][41], due to its merits for practical modelling of large-scale structures with low-cost sensor measurement and highly accurate displacement estimations [42][43]. Several studies have shown the superior applications of iFEM/iQS4 approach Coupling of peridynamics and inverse finite element method for shape sensing and crack propagation monitoring of plate structures for damage identification in monolithic/stiffened structures having isotropic/orthotropic material properties [44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Several shape sensing applications with iFEM are available in the literature, based both on numerical and experimental case studies. However, although strain sensors can be applied to the whole structure when dealing with numerical case studies [ 44 , 54 ], their number and locations are one of the main constraints for practical applications [ 39 , 55 ]. Hardware limitations frequently limit the number of sensors available and their installation is subordinated to practical reasons, such as access to the structure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to shape sensing, iFEM has been also extended to damage detection in an SHM framework with different approaches, such as load-independent damage indices [ 44 , 55 ], damage parameters based on the Von Mises strain [ 36 , 63 ], damage indices based on the pseudo-excitation approach [ 54 ], and artificial neural networks [ 64 ]. However, these approaches are able to identify the presence and, in some cases, the location of damage in the structure (both metallic and composites) but not estimate its size, which is still an unexplored area of iFEM applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation